Lieder zum Johannisfest 1916 in der Loge zur Einigkeit. (Danzig : [wydawca nieznany], 1916)
Druk z pieśniami.
Keywords: Masoni -- Polska -- Gdańsk -- 1900-1945 -- druki ulotne; Druki ulotne -- 1900-1945.; Druki ulotne